2016
DOI: 10.1038/hr.2015.152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metabolic syndrome components and their clustering on carotid atherosclerosis in a sample of the general Japanese population

Abstract: The objective of this study was to investigate the impact of metabolic syndrome (MS) on carotid atherosclerosis in a Japanese population. A total of 1727 subjects (805 males and 922 females) were included. Intima-media thickness (IMT) was measured using ultrasonography. To evaluate the independent determinants of IMT, a stepwise multiple regression analysis was employed that included age, current smoking habit, LDL-C, HbA1c and the MS components (SBP, DBP, TG, HDL-C, FBG, and WC) as independent variables. Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…Additionally, a statistically significant difference between the subgroup of smokers with DMt2 and those without DMt2 was found (1.01 vs. 0.92; p < 0.005). Of course, we know that cigarette smoking affects the development of atherosclerosis [ 34 , 35 ] and DMt2 intensifies this phenomenon but, in our study, we confirmed that this relationship also occurs in the group of patients at the highest cardiovascular risk.…”
Section: Discussionsupporting
confidence: 73%
“…Additionally, a statistically significant difference between the subgroup of smokers with DMt2 and those without DMt2 was found (1.01 vs. 0.92; p < 0.005). Of course, we know that cigarette smoking affects the development of atherosclerosis [ 34 , 35 ] and DMt2 intensifies this phenomenon but, in our study, we confirmed that this relationship also occurs in the group of patients at the highest cardiovascular risk.…”
Section: Discussionsupporting
confidence: 73%
“…However, according to the criterion of Japan-specific metabolic syndrome 33 ) , a person who does not have abdominal obesity is not diagnosed with metabolic syndrome even if he/she has all of the metabolic abnormalities. In this regards, some recent reports including our study have revealed that a clustering of the metabolic abnormalities is crucial irrespective of the presence or absence of abdominal obesity 38 , 39 , 40 ) . We, therefore, attempted to estimate the individual risk profile for CHD by assessing a clustering number of hypertension, dyslipidemia, glucose intolerance and hyperuricemia except for abdominal obesity.…”
Section: Discussionsupporting
confidence: 57%
“…, 30 Elshorbagy et al 31 identified a significant increase in carotid intima-media thickness in metabolic syndrome patients as compared to the non-metabolic syndrome obese and control groups. Hirata et al 32 demonstrated in a study, which included 1727 subjects, that an elevated number of metabolic syndrome components, with or without central obesity, was associated with higher intima-media thickness and, hypertension had the strongest association with higher intima-media thickness. Alp et al 33 found that carotid artery intima-media thickness was strongly associated with Tei index values.…”
Section: Discussionmentioning
confidence: 99%